2009
DOI: 10.1128/jb.01256-08
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pyogenesCovRS Mediates Growth in Iron Starvation and in the Presence of the Human Cationic Antimicrobial Peptide LL-37

Abstract: We found that the global regulatory two-component signal transduction system CovRS mediates the ability of group A streptococcus (GAS) to grow under two stresses encountered during infection: iron starvation and the presence of LL-37. We also showed that CovRS regulates transcription of the multimetal transporter operon that is important for GAS growth in a low concentration of iron.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 57 publications
1
28
0
Order By: Relevance
“…A full description of the CodY regulon will be the subject of a separate publication. The CovRS global regulator is one of the beststudied regulatory systems in GAS (14) and is known to respond to (i) the presence of cationic antimicrobial peptides (23,26), (ii) low pH, (iii) high temperature, and (iv) changes in ion concentration (like the presence of Mg 2ϩ or Fe) (17,25). It has been suggested that the main environmental signal is envelope stress (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A full description of the CodY regulon will be the subject of a separate publication. The CovRS global regulator is one of the beststudied regulatory systems in GAS (14) and is known to respond to (i) the presence of cationic antimicrobial peptides (23,26), (ii) low pH, (iii) high temperature, and (iv) changes in ion concentration (like the presence of Mg 2ϩ or Fe) (17,25). It has been suggested that the main environmental signal is envelope stress (23).…”
Section: Discussionmentioning
confidence: 99%
“…The CovRS global regulator is one of the beststudied regulatory systems in GAS (14) and is known to respond to (i) the presence of cationic antimicrobial peptides (23,26), (ii) low pH, (iii) high temperature, and (iv) changes in ion concentration (like the presence of Mg 2ϩ or Fe) (17,25). It has been suggested that the main environmental signal is envelope stress (23). A common route of GAS infection is invasion through the pharynx (51), where the cells are challenged with environmental fluctuations affecting not only the pH or ionic composition of the mucosal bathing saliva but also the availability of nutrients (9).…”
Section: Discussionmentioning
confidence: 99%
“…In group A Streptococcus (Streptococcus pyogenes, or GAS), CsrRS is a major global regulatory system that can repress as many as 15% of chromosomal genes, including a number of surface-associated and secreted proteins that mediate virulence and host-pathogen interactions (3,16,18,33,39). Mg 2ϩ and the human cathelicidin antimicrobial peptide LL-37 have been identified as opposing signals that act through CsrS to regulate an extensive repertoire of GAS genes (17,(20)(21)(22). An orthologue of the CsrRS system has been identified in GBS (27,31).…”
mentioning
confidence: 99%
“…For most histidine kinases, this process is also reversible, since the histidine kinase can act as a phosphatase to remove the phosphate from the aspartate residue of its cognate response regulator. One of the TCSs studied in GAS is CovRS (control of virulence) (17), which is critical for growth under many stress conditions (general stress response) (8,9,18) and appears to respond to membrane stress. The CovRS system appears to be pivotal in determining disease outcome (24,28,69).…”
mentioning
confidence: 99%